Lithium slag-based cementing material and preparation method thereof
The method addresses the environmental and utilization challenges of lithium slag by preparing a cementitious material through washing, chemical stimulation, and mechanical activation, improving its performance and safety for sustainable disposal.
Patent Information
- Application Number
- CN202410976540.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium slag, an industrial waste from lithium ore extraction, is not effectively utilized and poses environmental hazards due to its high alkali content and component fluctuations, leading to land occupation and pollution risks.
A method involving water washing, de-alkalization, chemical stimulation, and mechanical activation of lithium slag to produce a lithium slag-based cementitious material, which includes mixing pretreated lithium slag with cement clinker and activators to enhance hydration activity and reduce alkali content.
The method improves the utilization and safety of lithium slag by enhancing its hydration activity, allowing it to replace silicate cement and reducing CO2 emissions while ensuring harmless disposal and resource efficiency.
Smart Images

Figure CN119118546A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid waste recycling, and in particular to a lithium slag-based gelling material and a preparation method thereof. Background Art
[0002] Lithium slag is an industrial solid waste produced during the extraction of lithium from lithium ore. Yichun, Jiangxi Province has the world's largest lithium mica mine, which is converted into lithium oxide with a reserve of about 1.1 million tons, accounting for more than 30% of the country's lithium resource reserves. At present, most lithium slag is treated by stockpiling, and the accumulation of lithium slag not only occupies a large amount of land and harms the ecological environment, but also endangers the health of local residents. In addition, lithium slag contains a large amount of heavy metals and harmful substances. If not specially treated, heavy metals in lithium slag will seep out in large quantities, pollute groundwater and soil, and further endanger human health through the migration and transformation of heavy metals in animals and plants. Therefore, it is urgent to comprehensively utilize lithium slag. The main chemical components of lithium slag are SiO2 and Al2O3, and it has certain volcanic ash activity and good micro-aggregate filling effect. Therefore, preparing building materials is one of the effective ways to improve utilization efficiency. It can be used as a raw material for alkali-activated cementitious materials, but the characteristics of lithium slag limit its dosage. Summary of the invention
[0003] The present application provides a lithium slag-based cementitious material having a large amount of lithium slag and a preparation method thereof, which is conducive to resource utilization, high performance and harmless utilization.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a lithium slag-based gelling material, the preparation method comprising:
[0005] The lithium slag will be subjected to water washing and de-alkali treatment;
[0006] Chemically stimulating and drying the lithium slag after water washing and de-alkali treatment;
[0007] The dried lithium slag is ground and activated to obtain pre-treated lithium slag;
[0008] Pretreated lithium slag, industrial solid waste, cement clinker and activator are mixed in proportion to form a lithium slag-based cementitious material; wherein the content of the pretreated lithium slag in terms of mass percentage is [30%, 60%].
[0009] According to the first aspect, in a possible implementation, the step of washing and de-alkalizing the lithium slag includes:
[0010] Mixing lithium slag and clean water according to a preset solid-liquid ratio to form lithium slag slurry;
[0011] Soaking for 4 hours to 40 hours at a temperature of 20° C. to 60° C., filtering the lithium slag slurry to separate the lithium slag;
[0012] The separated lithium slag is washed multiple times;
[0013] The preset solid-liquid ratio is between (1:1) and (1:9), and the number of washing times is between 1 and 10.
[0014] According to the first aspect, in a possible implementation, the step of chemically exciting and drying the lithium slag after water washing and de-alkalization comprises:
[0015] The lithium slag after water washing and de-alkali treatment is added into a Ca(OH)2 solution with a pH value of 10 to 13;
[0016] Stir at a speed of 200 r / min to 600 r / min for 2 h to 4 h;
[0017] filtering and separating lithium slag from the solution;
[0018] The filtered lithium slag is dried until the moisture content is less than 3%.
[0019] According to the first aspect, in a possible implementation, the step of grinding and activating the dried lithium slag to obtain the pretreated lithium slag includes:
[0020] The dried lithium slag is mixed with a grinding aid and an enhancing agent for grinding and activation until the specific surface area of the lithium slag is 500m2 / kg to 800m2 / kg;
[0021] The grinding aid and enhancer is added in an amount of 0.01% to 0.05% of the lithium slag, and the grinding aid and enhancer comprises one or more of diethanol monoisopropanolamine, triisopropanolamine, calcium formate, calcium chloride and sucrose.
[0022] According to the first aspect, in a possible implementation, the industrial solid waste has a content of 20% to 40% by mass; the cement clinker has a content of 2% to 10% by mass; and the activator has a content of 4% to 10% by mass.
[0023] According to the first aspect, in a possible implementation, the industrial solid waste includes one or more of slag, fly ash, steel slag and desulfurization gypsum.
[0024] According to the first aspect, in a possible implementation, the specific surface area of the industrial solid waste is [400m2 / kg~700m2 / kg].
[0025] According to the first aspect, in a possible implementation manner, the activator includes one or more of NaOH, KOH, Ca(OH)2, Na2SiO3, CaSO4, Na2CO3 and CaCO3.
[0026] According to the first aspect, in a possible implementation manner, the cement clinker includes silicate cement clinker and sulphoaluminate cement clinker.
[0027] In a second aspect, an embodiment of the present application further provides a lithium slag-based gelling material, wherein the lithium slag-based gelling material is made by the preparation method of the lithium slag-based gelling material described in the first aspect.
[0028] The lithium slag-based cementitious material and preparation method provided by the present application improve the problems of low hydration activity, high alkali content and large fluctuation of components of lithium slag by pre-treating lithium slag by water washing, de-alkaliation, chemical excitation and mechanical activation, so as to realize resource utilization, high performance and harmless utilization of large amount of lithium slag in the process of preparing cementitious material. In addition, lithium slag-based cementitious material is used to replace silicate cement, so as to realize the recycling of lithium slag solid waste and reduce CO2 emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 It is a schematic flow chart of a method for preparing a lithium slag-based gelling material in one embodiment of the present application. DETAILED DESCRIPTION
[0031] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0034] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0035] In a first aspect, the present application provides a method for preparing a lithium slag-based gelling material, such as Figure 1 As shown, the preparation method comprises the following steps:
[0036] Step S10, washing and de-alkali treatment of the lithium slag;
[0037] The lithium slag is mixed with clean water at a preset solid-liquid ratio (e.g., 1:1 to 1:9) to form a lithium slag slurry; the slag is soaked at a temperature of 20°C to 60°C for 4h to 40h to fully dissolve the soluble salt in the water, and the lithium slag and solution in the lithium slag slurry are separated by filtering or centrifugation; the separated lithium slag is washed for multiple times, the number of washings can be 1 to 10 times, until the concentration of alkali metal ions in the washing liquid reaches an acceptable level. The number of washings is usually 2 to 5 times.
[0038] It should be noted that the solid-to-liquid ratio is the ratio of the mass of lithium slag to the volume of clean water. The solid-to-liquid ratio range is determined according to actual production needs and test results. Specifically, it is adjusted according to factors such as the alkali content, impurity type and content of the lithium slag, and is usually between (1:1) and (1:9). The solid-to-liquid ratio determines the concentration of the lithium slag slurry, which in turn affects the effect of subsequent immersion and washing. Pour the weighed lithium slag and clean water into the mixing equipment, and stir thoroughly to evenly disperse the lithium slag in the water to form a lithium slag slurry.
[0039] The choice of soaking temperature should take into account factors such as the dissolution rate of soluble salts in the lithium slag, energy consumption, and equipment requirements, while avoiding adverse effects of excessively high temperatures on the lithium slag. The soaking time of the lithium slag slurry in a constant temperature environment can be selected between 4 hours and 40 hours based on factors such as the alkali content, particle size distribution, characteristics of the lithium slag, and the desired dealkalization effect of the lithium slag. A longer soaking time helps to more thoroughly remove the soluble salts in the lithium slag, but it will also increase production costs and equipment occupancy time.
[0040] The lithium slag slurry after soaking is separated into solid and liquid using filters, centrifuges and other equipment, so as to separate the lithium slag from the aqueous solution containing soluble salts. The separated lithium slag will be used for subsequent washing and treatment; while the aqueous solution may contain a certain amount of alkali metal ions and other impurities, which need to be properly handled or recycled according to environmental protection requirements.
[0041] In order to further remove the soluble salts and other impurities attached to the surface of the lithium slag, the filtered lithium slag needs to be washed multiple times. The number of washings can be selected between 1 and 10 times according to the cleanliness requirements of the lithium slag and the production process conditions. Clean water or a weak acid solution (such as a dilute acetic acid solution) can be used for washing to neutralize the alkaline substances on the surface of the lithium slag and promote the dissolution and shedding of impurities. Sufficient solid-liquid separation should be performed after each washing to ensure the washing effect and reduce the waste of water resources.
[0042] By washing with water, the soluble alkali metal ions in the lithium slag are washed away by the solubility of water, and the soluble alkali metal ions (such as Na + , K + etc.), reduce the possibility of alkali metal ions interfering with or reducing the performance of subsequent materials, and improve the purity of lithium slag.
[0043] Step S20, chemically exciting and drying the lithium slag after washing and de-alkali treatment;
[0044] The lithium slag after water washing and de-alkali treatment is added into a Ca(OH)2 solution with a pH value of 10 to 13; the strong alkaline environment of calcium hydroxide (Ca(OH)2) is utilized to promote the dissolution and repolymerization reaction of aluminosilicate minerals in the lithium slag, thereby improving the activity of the lithium slag.
[0045] The choice of pH value depends on the mineral composition of lithium slag and the expected stimulation effect. A higher pH value helps to accelerate the dissolution of minerals in lithium slag, but it may also make the solution too viscous and affect the stirring effect. Note that the amount of lithium slag added should be controlled within a certain range to ensure the concentration of the solution and the stirring effect.
[0046] Stir at a speed of 200r / min to 600r / min for 2h to 4h; the speed and stirring time should be determined according to the particle size distribution of lithium slag, the concentration of the solution and the performance of the stirring equipment. Higher speed and longer stirring time are conducive to the uniform dispersion and full reaction of lithium slag particles in the solution, but they will also increase energy consumption and equipment wear.
[0047] Filter and separate the lithium slag in the solution; after stirring, use filtering equipment (such as filter screen, filter cloth, etc.) to separate the solid particles in the solution (i.e., the excited lithium slag) from the solution. During the filtration process, ensure that the pore size of the filter screen is moderate to avoid clogging and loss of lithium slag particles.
[0048] The filtered lithium slag is dried to a moisture content of less than 3% to remove excess moisture. The drying method can be natural drying, hot air drying or vacuum drying. The drying temperature and time should be determined according to the moisture content of the lithium slag and the performance of the drying equipment to ensure that the lithium slag reaches the required degree of dryness and avoid agglomeration and increased energy consumption caused by excessive moisture during the grinding process.
[0049] Add an appropriate amount of chemical activator (such as alkaline activator, sulfate activator, water glass, etc.) to the lithium slag, and carry out chemical activation reaction under certain conditions (such as stirring, heating, etc.) to transform the mineral components in the lithium slag and improve the activity. The activated lithium slag is dried, usually by hot air drying or natural drying, to remove the moisture therein and ensure that the moisture content of the lithium slag drops to a certain level (such as less than 3%) to facilitate the subsequent grinding and activation process.
[0050] In this application, Ca(OH)2 is used for chemical excitation, and calcium ions (Ca 2+ ) will undergo a replacement reaction with the remaining potassium (K) and sodium (Na) salts in the lithium slag. In this process, K and Na ions are replaced, thereby reducing the alkalinity of the lithium slag and achieving the purpose of dealkalization. At the same time, calcium sulfate (CaSO4) generated by the replacement reaction will remain in the lithium slag.
[0051] At the same time, calcium sulfate plays an important stimulating role in lithium slag cementitious materials. It can react with components such as aluminosilicates in lithium slag to generate more hydration products, such as CSH (calcium silicate hydrate) gel. These hydration products can fill the pores of the material to improve the density and strength of the material. At the same time, the addition of calcium sulfate can also promote the solidification of heavy metal ions in lithium slag, fixing them in the (N,C)-ASH three-dimensional network structure, thereby improving the environmental performance of the material.
[0052] It should be noted that during the entire chemical excitation process, the pH value of the Ca(OH)2 solution, the amount of lithium slag added, the stirring speed and time and other parameters should be strictly controlled to ensure the consistency and stability of the excitation effect. During the stirring process, the state of the solution and the stirring effect should be carefully observed, and the stirring parameters should be adjusted in time to avoid agglomeration and precipitation of lithium slag particles. The dried lithium slag should be properly stored to avoid moisture and contamination for subsequent use.
[0053] Step S30, grinding and activating the dried lithium slag to obtain pre-treated lithium slag;
[0054] The dried lithium slag is mixed with a grinding aid and an enhancing agent for grinding and activation until the specific surface area of the lithium slag is 500m2 / kg to 800m2 / kg;
[0055] Use ball mill, vertical mill and other grinding equipment to grind the dried lithium slag. Control the grinding time and grinding fineness to obtain pre-treated lithium slag with suitable particle size distribution and specific surface area. After grinding, the ground lithium slag is screened to remove oversized or undersized particles to ensure product quality.
[0056] According to the amount of lithium slag and the expected effect, add an appropriate amount of grinding aid to the lithium slag. The amount of grinding aid is usually 0.01% to 0.05% of the mass of the lithium slag. The grinding aid can be selected from one or more combinations of diethanol monoisopropanolamine, triisopropanolamine, calcium formate, calcium chloride and sucrose. These ingredients can play a role in lubricating, dispersing and enhancing the activity of lithium slag during the grinding process.
[0057] The mixed lithium slag and grinding aid are sent to a ball mill or vertical mill for grinding. The choice of grinding method should be based on comprehensive considerations of production scale, equipment performance and cost-effectiveness. During the grinding process, the lithium slag particles are gradually refined by controlling parameters such as grinding time and mill speed, and the specific surface area reaches 500m 2 / kg~800m 2 / kg. This specific surface area range helps lithium slag to better perform its performance in subsequent applications.
[0058] The dried lithium slag is ground through a grinding machine. Through strong mechanical impact, shearing, grinding, mutual extrusion and collision between particles, the crystal particles can be refined and the depolymerization of active silicon oxide and aluminum oxide in the lithium slag can be promoted. In addition, the addition of triisopropanolamine can stimulate the volcanic ash effect of lithium slag and improve the hydration activity of lithium slag; the ground lithium slag is the pre-treated lithium slag.
[0059] Step S40, mixing the pretreated lithium slag, industrial solid waste, cement clinker and activator in proportion to form a lithium slag-based cementitious material; wherein the pretreated lithium slag has a mass percentage content of [30%, 60%].
[0060] The invention pre-treats the lithium slag by water washing, de-alkali treatment, chemical excitation and mechanical activation to improve the problems of low hydration activity, high alkali content and large component fluctuation of the lithium slag, so as to realize resource utilization, high performance and harmless utilization of high-doped lithium slag in the process of preparing cementitious materials.
[0061] In addition, lithium slag-based cementitious materials are used to replace silicate cement, which can achieve the recycling of lithium slag solid waste and reduce CO2 emissions.
[0062] The industrial solid waste content is 20% to 40% by mass; industrial solid waste can be used as an important component, and its content can be flexibly adjusted according to specific application requirements, raw material properties and product performance requirements. A higher industrial solid waste content helps reduce production costs and realizes the resource utilization of waste, which is in line with the concept of sustainable development.
[0063] The industrial solid waste includes one or more of slag, fly ash, steel slag and desulfurization gypsum. Slag is mainly composed of minerals such as silicates and aluminates, has high volcanic ash activity, and can react with alkaline stimulants such as lime to generate hydration products with gelling properties. Fly ash mainly comes from waste from coal-fired power plants, contains a large amount of active ingredients such as silicon dioxide and aluminum oxide, also has volcanic ash activity, and can improve the performance of materials. Steel slag is waste generated in the process of steel production, containing multiple elements such as iron, calcium, magnesium, silicon, aluminum, etc. Its mineral composition is complex, but it also has certain activity and can be used to prepare cementitious materials. Desulfurization gypsum is mainly used for waste generated in the process of flue gas desulfurization. Its main component is calcium sulfate, which has an stimulating effect, can promote the hydration reaction, and improve the strength of the material.
[0064] When preparing lithium slag-based cementitious materials, the appropriate types of industrial solid waste and their proportions can be selected according to the supply of raw materials, costs and product performance requirements. The addition of these industrial solid wastes not only helps to reduce production costs, but also can react with the components in lithium slag through their active ingredients to generate more hydration products, thereby improving the strength and durability of the material.
[0065] The specific surface area of the industrial solid waste is [400m2 / kg~700m2 / kg]. For industrial solid waste, in the preparation process of lithium slag-based cementitious materials, the specific surface area of the industrial solid waste has a significant impact on the performance of the material. A larger specific surface area helps to evenly disperse the solid waste particles in the mixed system, reduce the agglomeration phenomenon between particles, and improve the uniformity and stability of the mixed system. At the same time, a larger specific surface area can also promote the full contact and reaction of the solid waste particles with components such as activators and cement clinkers, accelerate the process of hydration reactions, and generate more hydration products. These hydration products can fill the pores and cracks inside the material to improve the density and strength of the material.
[0066] The specific surface area of industrial solid waste is affected by many factors, including the type, source, particle size distribution, preparation method, and subsequent treatment process of the solid waste. For example, physical methods such as mechanical grinding or ultrafine grinding can reduce the particle size of solid waste particles, thereby increasing their specific surface area; while chemical modification or heat treatment can change the surface properties of solid waste particles and further improve their reactivity.
[0067] The content of the activator is a key parameter that directly affects the performance and reactivity of the material. The activator content of 4% to 10% by mass is based on a large number of experimental studies and practical application experience, aiming to ensure that the activator can fully play its role while avoiding the adverse effects that may be caused by excessive use.
[0068] According to the first aspect, in a possible implementation manner, the activator includes one or more of NaOH, KOH, Ca(OH)2, Na2SiO3, CaSO4, Na2CO3 and CaCO3.
[0069] Alkaline activators (such as NaOH, KOH, Ca(OH)2): These substances can neutralize the acidic components in lithium slag and increase the pH value of the reaction system, which is beneficial to the dissolution of aluminosilicates in lithium slag and the stimulation of volcanic ash activity.
[0070] Sodium silicate (Na2SiO3): Sodium silicate can not only provide a silicon source and promote the formation of hydration products such as hydrated calcium silicate, but also react with aluminates in lithium slag to form gelling compounds.
[0071] Calcium sulfate (CaSO4): Calcium sulfate plays an important regulatory role in the cement hydration process. It can promote the formation of CSH gel and may react with other components to generate new hydration products.
[0072] Sodium carbonate and calcium carbonate (Na2CO3, CaCO3): These substances can release CO2 during hydration, promoting the hardening and strength development of materials. At the same time, they may also participate in other chemical reactions to generate compounds that are beneficial to the performance of the material.
[0073] In the preparation process of lithium slag cementitious materials, adding an appropriate amount of activator can not only stimulate the volcanic ash activity of lithium slag, but also promote the chemical reaction between heavy metal ions and other components in lithium slag. The stable compounds generated by these reactions can be firmly fixed in the (N,C)-ASH three-dimensional network structure, thereby effectively preventing the migration and diffusion of heavy metal ions in the environment. This solidification mechanism is of great significance for improving the environmental protection and safety of materials, especially when treating industrial solid waste containing heavy metal ions.
[0074] The cement clinker content is 2% to 10% by mass; cement clinker is one of the main strength sources in cementitious materials. Its hydration reaction can generate a large amount of hydration products, such as calcium silicate hydrate (CSH) gel, etc., which contribute significantly to the strength of the material. The content of cement clinker also affects the properties of the material such as setting time, hardening rate and durability. By adjusting the content of cement clinker, precise control of material properties can be achieved.
[0075] When the content of cement clinker is low (2% to 5%), cement clinker mainly plays an exciting and catalytic role. It can react with the active ingredients in industrial solid wastes such as lithium slag to promote the formation of hydration products. Due to the low content of cement clinker, the cost of the material is relatively low, which is conducive to reducing the overall project cost. When the content of cement clinker is in the middle (5% to 10%): Within this range, cement clinker can provide sufficient strength source and form a good synergistic effect with industrial solid wastes such as lithium slag. The early strength and late strength of the material can be well guaranteed to meet the needs of most projects. An appropriate amount of cement clinker can also improve the density and durability of the material and reduce the formation of pores and cracks.
[0076] Cement clinker includes silicate cement clinker and sulphoaluminate cement clinker. Portland cement clinker is a common type of cement clinker, mainly composed of minerals such as tricalcium silicate (C3S), dicalcium silicate (C2S), tricalcium aluminate (C3A) and tetracalcium aluminoferrate (C4AF). Portland cement clinker has high strength and durability and is the main raw material for preparing ordinary cement and special cement. In lithium slag-based cementitious materials, Portland cement clinker can provide the necessary strength and hardening properties, while reacting with the active ingredients in lithium slag and industrial solid waste to generate more hydration products. Sulphoaluminate cement clinker is a cement clinker with anhydrous calcium sulphoaluminate and dicalcium silicate as the main minerals. It has excellent properties such as early strength, high strength, frost resistance and impermeability, and is particularly suitable for projects requiring rapid hardening. In lithium slag-based cementitious materials, the addition of sulphoaluminate cement clinker can significantly improve the early strength and hardening speed of the material, and react with other components to generate a denser microstructure, thereby improving the overall performance of the material.
[0077] When preparing lithium slag-based cementitious materials, it is necessary to comprehensively consider the properties, costs and performance requirements of various raw materials. By adjusting the content ratio of industrial solid waste, cement clinker and activator, lithium slag-based cementitious materials with different performance characteristics can be prepared. At the same time, attention should also be paid to the mixing uniformity of raw materials and the control of preparation process to ensure the quality and stability of the final product.
[0078] In addition, it should be noted that the specific ratio may need to be adjusted according to the actual situation. For example, different types of industrial solid waste and stimulants may have different effects on material properties, so it is necessary to optimize the selection based on the test results. At the same time, the temperature, humidity and other conditions during the preparation process may also affect the performance of the material and need to be strictly controlled.
[0079] In summary, the content ratio range of industrial solid waste, cement clinker and activator has a certain flexibility and can be adjusted and optimized according to specific application requirements and test results.
[0080] The present application is described below by embodiments:
[0081] Embodiment 1: The lithium slag is washed and de-alkalized under the conditions of solid-liquid ratio of 2:1, washing temperature of 20°C, soaking time of 6h, washing once, and then the washed lithium slag is put into Ca(OH)2 solution of pH=10, the speed is 200r / min, and the stirring time is chemical-de-alkalization / excitation under the conditions. Finally, the treated lithium slag and the lithium slag with 0.04% grinding aid (wherein the grinding aid is triisopropanolamine) are ball milled for 10min to obtain pretreated lithium slag, which is marked as L-1.
[0082] Embodiment 2: The lithium slag is washed and de-alkalized under the conditions of solid-liquid ratio of 5:1, washing temperature at 20°C, soaking time for 6h, washing once, and then the washed lithium slag is placed in a Ca(OH)2 solution with a pH of 10, a rotation speed of 200r / min, and a stirring time of 2h for chemical-de-alkalization / excitation. Finally, the treated lithium slag and a grinding aid enhancer (wherein the grinding aid enhancer is triisopropanolamine) with a lithium slag dosage of 0.04% are ball-milled for 10min to obtain a pretreated lithium slag, which is marked as L-2.
[0083] Embodiment 3: The lithium slag is washed and de-alkalized under the conditions of solid-liquid ratio of 5:1, washing temperature of 20°C, soaking time of 6h, and washing 5 times, and then the washed lithium slag is put into Ca(OH)2 solution of pH=10, the rotation speed is 200r / min, and the stirring time is chemical-de-alkalization / excitation under the conditions. Finally, the treated lithium slag and the lithium slag with 0.04% grinding aid enhancer (wherein the grinding aid enhancer is triisopropanolamine) are ball-milled for 10min to obtain pretreated lithium slag, which is marked as L-3.
[0084] Embodiment 4: Wash and de-alkali the lithium slag under the conditions of solid-liquid ratio of 5:1, washing temperature at 20°C, soaking time of 6h, washing 5 times, then put the washed lithium slag into Ca(OH)2 solution of pH=10, speed of 200r / min, stirring time of 2h, chemical-de-alkali / excitation, finally, the treated lithium slag and lithium slag with 0.04% grinding enhancer (wherein the grinding enhancer is triisopropanolamine, calcium formate and sucrose, the ratio of the three is 50:40:10)) are ball milled for 10min to obtain pretreated lithium slag, marked as L-4.
[0085] Table 1: Raw material content of each component / % Specific surface area / m2 / kg 28d activity index / %
[0086]
[0087] Note: L-0 is lithium slag without pretreatment
[0088] The preparation of high-doped lithium slag gelling material includes the following embodiments:
[0089] Example 5: Application of high-doped lithium slag in preparing cementitious materials, the preparation method thereof comprises the following steps:
[0090] (1) 40 parts of pretreated lithium slag L-4, 40 parts of mineral powder (wherein the specific surface area of the mineral powder is 500 m2 / kg), 10 parts of cement clinker (wherein the specific surface area of ordinary Portland cement clinker and sulphoaluminate cement is about 370 m2 / kg, and the ratio of the two is 8:2), 4 parts of calcium hydroxide, 4 parts of sodium hydroxide, and 2 parts of sodium carbonate are put into a mixer and fully mixed for 4 hours to obtain a high-dosage lithium slag-based cementitious material.
[0091] (2) According to the weight ratio, 450 parts of the lithium slag-based cementitious material obtained in the above step (1), 1350 parts of standard sand and 225 parts of tap water are put into a mortar mixer and mixed evenly according to the standard GB / T17671-2021. The mortar is molded and loaded into a triple mold. After 1 day, the mold is removed and finally placed in a standard curing box for curing for 28 days.
[0092] Comparative Example 6: Application of high-doped lithium slag in preparing cementitious materials, wherein the preparation method comprises the following steps:
[0093] (1) 40 parts of untreated lithium slag L-0, 40 parts of mineral powder (wherein the specific surface area of the mineral powder is 500 m2 / kg), 10 parts of cement clinker (wherein the specific surface area of ordinary Portland cement clinker and sulphoaluminate cement is about 370 m2 / kg, and the ratio of the two is 8:2), 4 parts of calcium hydroxide, 4 parts of sodium hydroxide, and 2 parts of sodium carbonate are put into a mixer and fully mixed for 4 hours to obtain a high-dosage lithium slag-based cementitious material.
[0094] (2) According to the weight ratio, 450 parts of the lithium slag-based cementitious material obtained in the above step (1), 1350 parts of standard sand and 225 parts of tap water are put into a mortar mixer and mixed evenly according to the standard GB / T17671-2021. The mortar is molded and loaded into a triple mold. After 1 day, the mold is removed and finally placed in a standard curing box for curing for 28 days.
[0095] The comparison and examples were tested in accordance with the requirements of GB175-2023 of General Portland Cement.
[0096]
[0097] As shown in the table above, based on the calculation that CO2 emissions from 1 ton of Portland cement are approximately 0.5 t to 0.7 t, the carbon reduction per ton of Example 5 is 0.45 t to 0.63 t.
[0098] In addition, the present application also provides a lithium slag-based gelling material, which is prepared by the preparation method of the lithium slag-based gelling material described above. The present invention improves the problems of low hydration activity, high alkali content and large fluctuation of components of lithium slag by pre-treating the lithium slag by water washing and de-alkali-chemical excitation-mechanical activation. The content of pre-treated lithium slag in the lithium slag-based gelling material can reach [30%, 60%] by mass percentage, realizing resource utilization, high performance and harmless utilization of large-volume lithium slag in the process of preparing gelling materials.
[0099] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a lithium slag-based gelling material, characterized in that: The preparation method comprises: The lithium slag is subjected to water washing and de-alkali treatment; Chemically exciting and drying the lithium slag after water washing and de-alkali treatment; Grinding and activating the dried lithium slag to obtain pretreated lithium slag; Pretreated lithium slag, industrial solid waste, cement clinker and activator are mixed in proportion to form a lithium slag-based cementitious material; wherein the content of the pretreated lithium slag in terms of mass percentage is [30%, 60%].
2. The method for preparing the lithium slag-based gelling material according to claim 1, characterized in that: The step of washing and de-alkalizing the lithium slag comprises: Mixing lithium slag and clean water according to a preset solid-liquid ratio to form lithium slag slurry; Soaking for 4 hours to 40 hours at a temperature of 20° C. to 60° C., filtering the lithium slag slurry to separate the lithium slag; The separated lithium slag is washed multiple times; The preset solid-liquid ratio is between (1:1) and (1:9), and the number of washing times is between 1 and 10.
3. The method for preparing the lithium slag-based gelling material according to claim 2, characterized in that: The step of chemically exciting and drying the lithium slag after water washing and de-alkalization comprises: The lithium slag after water washing and de-alkali treatment is added into a Ca(OH)2 solution with a pH value of 10 to 13; Stir at a speed of 200 r / min to 600 r / min for 2 h to 4 h; filtering and separating lithium slag from the solution; The filtered lithium slag is dried until the moisture content is less than 3%.
4. The method for preparing the lithium slag-based gelling material according to claim 3, characterized in that: The step of grinding and activating the dried lithium slag to obtain pre-treated lithium slag comprises: The dried lithium slag is mixed with a grinding aid and an enhancing agent for grinding and activation until the specific surface area of the lithium slag is 500m2 / kg to 800m2 / kg; The grinding aid and enhancer is added in an amount of 0.01% to 0.05% of the lithium slag, and the grinding aid and enhancer comprises one or more of diethanol monoisopropanolamine, triisopropanolamine, calcium formate, calcium chloride and sucrose.
5. The method for preparing a lithium slag-based cementitious material according to any one of claims 1 to 4, characterized in that: The industrial solid waste has a content of 20% to 40% by mass; the cement clinker has a content of 2% to 10% by mass; and the activator has a content of 4% to 10% by mass.
6. The method for preparing a lithium slag-based cementitious material according to any one of claims 1 to 4, characterized in that: The industrial solid waste includes one or more of slag, fly ash, steel slag and desulfurization gypsum.
7. The method for preparing a lithium slag-based cementitious material according to any one of claims 1 to 4, characterized in that: The specific surface area of the industrial solid waste is [400m2 / kg~700m2 / kg].
8. The method for preparing a lithium slag-based gelling material according to any one of claims 1 to 4, characterized in that: The activator comprises one or more of NaOH, KOH, Ca(OH)2, Na2SiO3, CaSO4, Na2CO3 and CaCO3.
9. The method for preparing a lithium slag-based gelling material according to any one of claims 1 to 4, characterized in that: The cement clinker includes silicate cement clinker and sulphoaluminate cement clinker.
10. A lithium slag-based gelling material, characterized in that: The lithium slag-based gelling material is prepared by the preparation method of the lithium slag-based gelling material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Special carbon-reducing auxiliary agent for low-calcium cement
CN116239326A
Low-carbon cement prepared from modified lithium slag composite multi-source solid waste, and method and application thereof
CN117069400A
Manufacture method of ceramic foam which superior to insulating effect by using by waste and natural gypsum.
KR100955621B1
Cited By
Ultrahigh-ductility lithium slag concrete and preparation method thereof
CN120157412A
Ultrahigh ductility lithium slag concrete and preparation method thereof
CN120157412B
Comprehensive recovery method of lithium slag
CN120714773A
